2023
DOI: 10.1186/s12889-023-15439-8
|View full text |Cite
|
Sign up to set email alerts
|

The perception of risk in contracting and spreading COVID-19 amongst individuals, households and vulnerable groups in England: a longitudinal qualitative study

Abstract: Background Social distancing restrictions to manage the COVID-19 pandemic were put in place from March 2020 in the United Kingdom (UK), with those classed as “highly clinically vulnerable” advised to shield entirely and remain at home. However, personal risk perception has been shown to comprise of various elements beyond those outlined in the national pandemic guidance. It is unclear whether those deemed COVID-19 vulnerable identified as high-risk to COVID-19 and thus complied with the relevan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 44 publications
0
4
0
Order By: Relevance
“…Qualitative studies may provide deeper insight into factors influencing risk perception during the COVID-19 pandemic. In a qualitative study from the United Kingdom, Hanna et al ( 2023 ) showed that people’s different views regarding COVID-19 emergence, transmission, and health consequences were partially inconsistent with the scientific consensus, and subjects themselves reported being overwhelmed by the abundance of information (Hanna et al, 2023 ). Also, subjects at high risk for severe COVID-19 disease estimated their individual risk to be low.…”
Section: Discussionmentioning
confidence: 99%
“…Qualitative studies may provide deeper insight into factors influencing risk perception during the COVID-19 pandemic. In a qualitative study from the United Kingdom, Hanna et al ( 2023 ) showed that people’s different views regarding COVID-19 emergence, transmission, and health consequences were partially inconsistent with the scientific consensus, and subjects themselves reported being overwhelmed by the abundance of information (Hanna et al, 2023 ). Also, subjects at high risk for severe COVID-19 disease estimated their individual risk to be low.…”
Section: Discussionmentioning
confidence: 99%
“…A major challenge for these models in evaluating future trends was forecasting the behavior of individuals, which was largely incorporated exogenously through changes in public health guidance. While public health guidance influenced behavior, several other endogenous factors, including age, gender, socioeconomics, health and wellbeing, and trust influenced risk perception and ultimately the behavior of individuals [ 3 , 4 ] but were largely lacking from models [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…The SARS-COV-2 pandemic has re-focused the attention of researchers on the relationship between preventive behaviour and risk perception 5 9 . Although risk perception has several definitions, it is typically defined as the subjective probability of the occurrence of an adverse event in the future and the expected magnitude of its consequences 10 .…”
Section: Introductionmentioning
confidence: 99%